2020
DOI: 10.24057/2071-9388-2019-143
|View full text |Cite
|
Sign up to set email alerts
|

Toward An Innovative Strategic Approach For Sustainable Management Of Natural Protected Areas In Italy

Abstract: As the world’s largest coordinated network of protected areas, the Natura 2000 network (N2k) encompasses the most valuable and threatened species and habitats in Europe. However, N2k sites have been often criticized due to their rigid management system that focuses only on conservation practice without a strategic vision for linking with the regional plans. This study aims to develop a novel approach for sustainable management of N2k sites in Italy by identifying existing gaps and developing conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…To plan for sustainable land cover utilization should be pushed for concrete action, requiring the surrounding communities and government agencies to find common ways to conserve the surrounding mangrove forests. In other words, coastal ecosystem planning should provide environmental resilience in line with Dastgerdi et al [25] that the system should be used is participation of highly qualified partnerships between local people and relevant government agencies; and stakeholders in a network of local communities cooperating to conserve the natural protected areas. Therefore, in the KEW areas, communities; entrepreneurs; and farmers living near the mangrove forest should be encouraged to take part in the maintenance of mangrove resources, along with the development of tourism in Krabi Province.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…To plan for sustainable land cover utilization should be pushed for concrete action, requiring the surrounding communities and government agencies to find common ways to conserve the surrounding mangrove forests. In other words, coastal ecosystem planning should provide environmental resilience in line with Dastgerdi et al [25] that the system should be used is participation of highly qualified partnerships between local people and relevant government agencies; and stakeholders in a network of local communities cooperating to conserve the natural protected areas. Therefore, in the KEW areas, communities; entrepreneurs; and farmers living near the mangrove forest should be encouraged to take part in the maintenance of mangrove resources, along with the development of tourism in Krabi Province.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, it is suitable for environmental research and able to monitor the changes very well. In addition to a technical study to find land cover in the KEW area that visualized the change in land cover in each period, Dastgerdi et al [25] has laid out a constructive strategic direction for sustainable environment management in the Umbria Region, Italy. The study results on solving environmental problems showed that participation of highly qualified partnerships between local people and relevant government agencies; and stakeholders in a network of local communities cooperating to conserve the natural protected areas will be able to sustainably solve environmental problems in the reservation area.…”
Section: Applied Environmental Researchmentioning
confidence: 99%
“…Plants nurture an entire world of soil organisms that feed and protect the plants according to aboveground-belowground, plant-soil feedbacks (PSFs) that have different spatio-temporal scales and are greatly affected by climaterelated factors (Ponge, 2013;Veen et al, 2019). The diverse communities of telluric bacteria and fungi keep the soil healthy and fertile and determine the main biogeochemical processes that make life possible on Earth (Dastgerdi et al, 2020;Sweeney et al, 2020;Wilpiszeski et al, 2019). They play fundamental roles in driving many ecosystem processes on which the functioning of terrestrial ecosystems depends on, including soil formation, nutrient and water cycling, climate regulation, carbon storage, production of food, medicine and fibre, disease and pest control, and greater resilience to global change (Bardgett & Van Der Putten, 2014;P.…”
Section: Soil Biological Quality/fertilitymentioning
confidence: 99%
“…-5.5 ° C under the HadCM3 A2 scenario (IPCC 2007). Under the current climate change situation, National Mitigation/Adaptation Plans and Policies should be implemented in watershed planning by the local authorities throughout the assessment, policy making, and implementation steps (Dastgerdi et al 2020) to deal with disasters that may occur in the NSW.…”
Section: Sensitivity Of Reservation Area To Deforestation In the Futurementioning
confidence: 99%
“…Waiyasusri and Chotpantarat 2020), not only by the growing population but also by conversion of forested areas for agricultural use. The area is characterized by the presence of low plains between valleys, which bring about the ease of access to the area (Benítez-López et al 2017;Clements et al 2014;Consiglio et al 2006), causing a rapid expansion of agricultural areas (Santiphop et al 2012;Trisurat et al 2019) and construction, leading to an increase in the economic status of the local communities and population (Hooke et al 2012;Lagrosa IV et al 2018;Sadler et al 2011). This has directly affected the land-use, as agricultural areas became replaced by recreational areas, hotels, accommodations and other structures, the number of which has increased in the NSW.…”
Section: Introductionmentioning
confidence: 99%